Blockchain and institutional complexity: an extended institutional approach. Issue 1 (16th February 2021) - Frolov, Daniil
Abstract: From a modern institutional economics viewpoint, blockchain is an institutional technology that minimizes transaction costs and greatly reduces intermediation. Through an analysis of blockchain, I demonstrate the possibilities of extended institutional approach – a new generation of complexity-focused methodologies and theories of institutional analysis that complement and expand the standard institutional paradigm. By using the theory of transaction value, I argue blockchain technologies not only will lead to a significant reduction in transaction costs but will also reorient intermediaries toward improving the quality of transactions and expanding the offer of additional transaction services. The theory of institutional assemblages indicates it is impossible to form a homogeneous system of blockchain-based institutions associated exclusively with the principles of decentralization, transparency, and openness. Blockchain-based institutions will be of a hybrid and conflicting nature, combining elements of opposing institutional logics – regulatory and algorithmic law, Ricardian and smart contracts, private and public systems, and uncontrollability and arbitration.